Doctoral thesis “The development of teenagers’ social skills" by Rita Raudeliūnaitė - Gudonis, Vytautas (Acta Paedagogica Vilnensia, 2007)
A review of a doctoral thesis by Rita Raudeliūnaitė.
Keywords: doctoral dissertation; development of social skills; disability